2017
DOI: 10.1159/000481853
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid S100B and Alzheimer’s Disease Biomarkers in Hip Fracture Patients with Delirium

Abstract: Objectives: This study aimed to investigate the relationship between cerebrospinal fluid (CSF) S100B astrocyte-derived protein and delirium and to perform stratified analyses according to clinical and CSF markers of dementia. Methods: We performed a prospective cohort study in a university hospital setting. The participants were patients admitted for hip fracture (n = 98) or for elective surgery (n = 50). Delirium was assessed daily perioperatively in hip fracture patients using the Confusion Assessment Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Neither CSF S100B nor GFAP have been much studied in terms of correlation with CSF core AD markers. Hov et al [32] found similar results among elective surgery patients free from dementia and delirium, with S100B positively correlating with P-tau but not with Aβ 42 in CSF. Ishiki et al [33] did not nd an association between GFAP and the core AD markers within a sample of healthy subjects and dementia patients.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Neither CSF S100B nor GFAP have been much studied in terms of correlation with CSF core AD markers. Hov et al [32] found similar results among elective surgery patients free from dementia and delirium, with S100B positively correlating with P-tau but not with Aβ 42 in CSF. Ishiki et al [33] did not nd an association between GFAP and the core AD markers within a sample of healthy subjects and dementia patients.…”
Section: Discussionmentioning
confidence: 70%
“…and GFAP with core AD markers in CSF. Hov et al [32] found an association between S100B and P-tau but not Aβ 42 among elective surgery patients free from dementia and delirium. Ishiki et al [33] did not nd an association between CSF GFAP and core markers within a dementia cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, stratification of delirium-afflicted patients suggests that CSF sTREM2 increases transiently prior to delirium onset, but then declines. An early but transient glial response in delirium is supported by increased levels of other CSF biomarkers of immune responses in incident delirium, such as neopterin [ 40 ] and astroglia-derived S-100β [ 41 ]. Thus, CSF sTREM2 is a promising biomarker of microglial activation that is presumably more usable to detect transient responses, which is consistent with TREM2 having a rapid cell surface turnover (< 1 h) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dissimilar study populations as well as lack of tissue specificity for both S100B and neuron-specific enolase may partly explain the divergent reports. Only a minority of the published studies [13, 14, 16] have been performed in cerebrospinal fluid (CSF) and, since extracerebral sources of S100B and neuron-specific enolase may influence blood levels, serum changes may not solely reflect upon brain damage [23]. One preliminary study on serum phosphorylated neurofilament-heavy, a structural protein in neurons, found an association between phosphorylated neurofilament-heavy and delirium severity [24].…”
Section: Introductionmentioning
confidence: 99%